Design Theory in Information Systems - Gregor, Shirley (Australasian Journal of Information Systems, 2002)
The aim of this paper is to explore an important category of information systems knowledge that is termed “design theory”. This knowledge is distinguished as the fifth of five types of theory: (i) theory for analysing and describing, (ii) theory for understanding, (iii) theory for predicting, (iv) theory for explaining and predicting, and (v) theory for design and action. Examples of design theory in information systems are provided, with associated research methods. The limited understanding and recognition of this type of theory in information systems indicates that further debate concerning its nature and role in our discipline is needed.